IMPLEMENTASI APLIKASI WEB SEBAGAI SISTEM INFORMASI GUDANG DI CAFÉ XYZ: Implementation of Web Applications as Information Systems Warehouse at Cafe XYZ - Hotmian Sitohang; Frengklin Matatula (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Currently the role of technology is growing rapidly in all fields of business. But not all businesses run businesses with technology, such as café nauli. Currently, café nauli still uses a system of collecting the supply of tub materials and stock manually with books. So that in the process of work takes quite a long time. Other risks are data loss and differences in expenditure and income of goods. Departing from the above problems, for this reason, the author implements an application for raw material inventory and stock to help facilitate data collection of goods in warehouses and minimize the risk of losing goods in cafes. The author uses the prototype system design method. This system is designed using PHP programming language and MySQL database. This research resulted in a web warehouse product for café Nauli in real time and up to date.